The precipitous decline of a gray fox population - Max R. Larreur; Clayton K. Nielsen; Damon B. Lesmeister; Guillaume Bastille-Rousseau (Global Ecology and Conservation)
Gray fox (Urocyon cinereoargenteus) populations have apparently declined across the Midwestern United States which may be reflected in their distributional patterns and occupancy. To assess the severity of gray fox population declines and potential changing space use patterns, we used two temporally independent datasets collected using camera traps at the same sites during 2008–2010 and 2022–2023 within a 16,058-km2 area of southern Illinois, USA. We then developed three predictive occupancy models that allowed comparison of gray fox spatial patterns and occupancy estimates over time. We assessed pairwise model predictive occupancy estimates using relative rank correlation and density plot overlap. Naïve occupancy (i.e., ndetected/nsurveyed) of gray fox declined from 0.20 to 0.06 between our two time periods. Predicted occupancy ranged from 0.01–0.47 to 0.11–0.43 between past and future spatial models, respectively, indicating stable gray fox occupancy and space use patterns. The contemporary model had predicted occupancy ranging from 0.02 to 0.10, a 4-fold decline in occupancy estimates across 99 % of our study extent. Most habitat features had different directional effects on gray fox occupancy between our two temporal periods, illustrating the complexity of gray fox habitat preferences and a shift in their ecology. Our study highlights the need for increased conservation and management of gray fox populations as their populations have indicated evident declines across the Midwest.